Activity patterns and habitat selection by terrestrial mammals in a mosaic landscape of silvopastoral system and forest fragments in the Andean piedmont in Colombia - Moreno Gabriela; Lizcano Diego J.; Sánchez Francisco (Folia Oecologica, 2025)
Traditional livestock ranching impacts biodiversity by fragmenting and isolating habitats first as habitat loss, then as habitat isolation, affecting local fauna that occupies native habitats that rely on forest. In degraded areas, silvopastoral systems (SPS) are an agroforestry practice that integrates trees and livestock and they could provide new habitats for this fauna, though their effects are not well understood for Neotropical mammalian assemblages. This study assessed habitat selection and activity patterns in the Andes piedmont of Colombia. Using camera traps, we evaluated records in an intervened area, which was located around two fragments of native forest. A total of 17 mammal species were recorded, with 5 species using the SPS, of which Cerdocyon thous was exclusive to the SPS, whereas 12 species were found only in the forest, including six carnivorous species. Two anteater species showed overlapping activity in the forest but different patterns in the SPS. Despite more anteater records in the forest, both species selected the SPS. These results suggest that SPS could benefit certain species and alter interactions among Neotropical mammals.